Second Annual Report of Severn Wildfowl Trust: 1948-1949 - Anonymous, Anonymous (Wildfowl, 1949)
No abstract available. Contents include the following: Map of the New Grounds, The Wild Geese, The Decoy, List of Birds Recorded at the New Grounds, Recoveries of Ringed Birds, The Waterfowl Collection, Visitors, Acknowledgements, Staff Arrangements, Director's Lectures, Publicity, Lease and License, Accommodation, Arrangements for Visitors, Minutes of the Second Annual Meeting, Balance Sheet, List of Members, Photographs, Key to the Wildfowl of the World.